Respuesta :
Hello, call me Emac.
Indeed, that is a very hard question! Here is how to answer it. Please hear this if it helps so I know. This helps, read it and if you don’t understand reply. I do have the answer, but try figuring it out first!
Simplifying
28 + -1(3c + 4) = 2(c + 6) + c
Reorder the terms:
28 + -1(4 + 3c) = 2(c + 6) + c
28 + (4 * -1 + 3c * -1) = 2(c + 6) + c
28 + (-4 + -3c) = 2(c + 6) + c
Combine like terms: 28 + -4 = 24
24 + -3c = 2(c + 6) + c
Reorder the terms:
24 + -3c = 2(6 + c) + c
24 + -3c = (6 * 2 + c * 2) + c
24 + -3c = (12 + 2c) + c
Combine like terms: 2c + c = 3c
24 + -3c = 12 + 3c
Solving
24 + -3c = 12 + 3c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-3c' to each side of the equation.
24 + -3c + -3c = 12 + 3c + -3c
Combine like terms: -3c + -3c = -6c
24 + -6c = 12 + 3c + -3c
Combine like terms: 3c + -3c = 0
24 + -6c = 12 + 0
24 + -6c = 12
Add '-24' to each side of the equation.
24 + -24 + -6c = 12 + -24
Combine like terms: 24 + -24 = 0
0 + -6c = 12 + -24
-6c = 12 + -24
Combine like terms: 12 + -24 = -12
-6c = -12
Divide each side by '-6'.
c =?
Indeed, that is a very hard question! Here is how to answer it. Please hear this if it helps so I know. This helps, read it and if you don’t understand reply. I do have the answer, but try figuring it out first!
Simplifying
28 + -1(3c + 4) = 2(c + 6) + c
Reorder the terms:
28 + -1(4 + 3c) = 2(c + 6) + c
28 + (4 * -1 + 3c * -1) = 2(c + 6) + c
28 + (-4 + -3c) = 2(c + 6) + c
Combine like terms: 28 + -4 = 24
24 + -3c = 2(c + 6) + c
Reorder the terms:
24 + -3c = 2(6 + c) + c
24 + -3c = (6 * 2 + c * 2) + c
24 + -3c = (12 + 2c) + c
Combine like terms: 2c + c = 3c
24 + -3c = 12 + 3c
Solving
24 + -3c = 12 + 3c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-3c' to each side of the equation.
24 + -3c + -3c = 12 + 3c + -3c
Combine like terms: -3c + -3c = -6c
24 + -6c = 12 + 3c + -3c
Combine like terms: 3c + -3c = 0
24 + -6c = 12 + 0
24 + -6c = 12
Add '-24' to each side of the equation.
24 + -24 + -6c = 12 + -24
Combine like terms: 24 + -24 = 0
0 + -6c = 12 + -24
-6c = 12 + -24
Combine like terms: 12 + -24 = -12
-6c = -12
Divide each side by '-6'.
c =?
c=2
28-(3c+4)=2(c+6)+c
1. get #'s out of parentheses
28-3c-4=2c+12+c
2. combine like terms
24-3c=3c+12
3. put the C's on one side and #'s on the other
subtract -12 from 24 and at +3c to the 3c
12=6c
4. then divide the 6 off to leave C all by itself
12/6=c
5. that gives you your answer
2=c